Optimization of Ni loading and operating conditions for carbon dioxide reforming of methane over NiO/CeO2 catalyst using response surface methodology - I Istadi; Nor Aishah Saidina Amin; Mohd Nizam Ahmad Sanusi (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2005)
Optimization of Ni loading and operating conditions for carbon dioxide reforming of methane over NiO/CeO2 catalyst using response surface methodologyModelling and optimization of Carbon Dioxide Reforming of Methane (CORM) reaction over NiO/CeO2 catalyst were developed using Response Surface Methodology (RSM). Relationship between responses, i.e. CH, conversion, H2 and CO selectivities, and three independent variables, i.e. reactor temperature, CO2/CH4 ratio, and wt. % Ni in the CeO-supported catalyst, were presented as empirical mathematical models. The models showed a good fitting to the experimental data statistically. The NiO/CeO2 showed a potential catalyst for the CORM process, though some coking formations were found. The catalysts exhibited a promising catalytic performance with the unity H2/CO ratio in the product, high methane conversion, and low reverse water gas shift reaction. The reactor temperature, CO2/CH4 ratio, and wt. % Ni in the CeO2-supported catalyst being 840oC, 1, and 6.5%, respectively were suggested with respect to CH4 conversion, H2 and CO selectivity, and H2/CO ratio of 75.7%, 68.5%, 54.5%, and 1.03, respectively. Keywords: Carbon dioxide reforming of methane, NiO/CeO, catalyst, Response Surface Methodology AbstrakPermodelan dan optimisasi reaksi pembentukan kembali metana dengan karbondioksida (CORM) melalui katalis NiO/CeO2 telah dikembangkan dengan menggunakan Response Surface Methodology (RSM). Hubungan antara respon-respon (konversi CH, selektifitas H2 and CO) dengan tiga peubah tak bergantung (temperatur reaktor; rasio CO2/CH4, dan % berat Ni dalam katalis berpenyangga CeO) dinyatakan dalam model matematika empiris. Model empiris tersebut secara statistik menunjukkan korelasi yang baik terhadap data-data eksperimen. NiO/CeO2 tersebut menunjukkan sebuah katalis yang berpotensi untuk proses CORM. Katalis tersebut menunjukkan kinerja katalitik yang menjanjikan dengan rasio H2/CO mendekati satu dalam produk, konversi metana yang tinggi, dan reaksi reverse water gas shift yang rendah. Temperatur reactor 840oC, rasio CO2/CH4, 1, dan 6.5 wt. % Ni adalah direkomendasikan dengan konversi CH4 75.7%, selektifitas H2 68.5%, selektifitas CO 54.5%, dan rasio H2/CO 1.03. Kata Kunci: Pembentukan kembali metana dengan karbondioksida, Katalis NiO/CeO2, Response Surface Methodology